The degree of exercise of academic freedom and its relationship to job satisfaction: ‎Al-Yarmouk University model - Al Alawneh, Khawla Mahmoud; Izhiman, Nidaa; Mokhemer Yahya, Shaima; El-Freihat, Sara Mohammad (Institute of Advanced Engineering and Science, 2025)
Academic freedom in Jordanian universities is the subject of debate and research, due to the policies of university education imposed within the country. However, academic freedom has been researched in Jordan for more than two years. This study aimed to find out the level of academic freedom practiced by faculty members at Yarmouk University and its relationship to job satisfaction from a point of view, as there was recently a difference in views on the exercise of academic freedom or the imposition of educational policies in Jordanian universities according to the views of academics. About 317 members of the university were selected in a simple random way. The correlational descriptive approach and a two-part questionnaire were used: the first part measures the degree of academic freedom exercised by faculty members in three areas (freedom of expression, research, and teaching). The second part measures the level of job satisfaction. The results indicated that the degree of academic freedom exercised by faculty members was high, as well as the level of job satisfaction, as it was found that faculty members were significantly satisfied with their jobs. There was also a correlation between the degree of academic freedom exercised by faculty members and the level of job satisfaction of faculty members. These results shed positive light on the policies adopted in the country to educate university students in order to continue to keep pace with global developments and global trends in university education and work to amend some university education policies with the concerned authorities.